A Descriptive Study of Hematologic Characteristics of Malaria Patients Attending A Tertiary Care Hospital in The Region of Kutch - Shah, Nidhi N; Sinha, Riti T. K (Annals of Pathology and Laboratory Medicine, 2019)
Background: In India, the epidemiology of malaria is complex because of geo-ecological diversity, multi-ethnicity, and wide distribution of nine anopheline vectors transmitting two commonest plasmodia species. Considering the fact, it is vital that every centre has its own demographic and pathological data about the profile of malaria patients in its catchment area. Methods: The present retrospective study was carried in the Department of Pathology, Gujarat Adani Institute of Medical Sciences (GAIMS), Bhuj for a period of one year. A total of 102 cases were included in the study. The blood samples were collected in Ethylenediamine tetra-acetic acid (EDTA) vacutainers and smears were prepared. Leishman staining and field staining on thick smears was done according to the published protocols. The diagnosis of malaria parasite was confirmed by a positive peripheral smear examination. Rings, schizonts and gametocytes of the malaria parasites (plasmodium vivax and plasmodium falciparum) were viewed for diagnosis. Thrombocytopenia was considered when the platelet count was less than 150 x 109/L and leucopenia when the total leucocyte count was less than 4,000 cells /cu mm. Result: In our study, 102 malaria positive cases were investigated for platelet count and total leucocyte count. Out of the 102 cases, male population was affected more than female. Out of the various malaria species, plasmodium vivax was the most prevalent (82.35%). The most common age group affected by various species varied, with age group of 1-10 years being most common for plasmodium falciparum cases, 21 to 30 years being most common for plasmodium vivax and 11 to 20 years being most common for mixed infection. All the cases of plasmodium falciparum were found to be with normal leucocyte count whereas in plasmodium vivax 82.14% cases were with normal leucocyte count and only 17.85% cases with leucopenia. Mixed infection had almost similar scenario with 71.42% cases with normal leucocyte count and 28.57% with leucopenia. In our study more number of cases of plasmodium falciparum was associated with thrombocytopenia (25%) as compared to plasmodium vivax (11.9%) and none in mixed infection. Conclusion: The high prevalence of malaria suggests the importance of timely diagnosis . The early identification of thrombocytopenia and leucopenia aids in timely management. This helps to decrease complicated malaria cases and its related mortality.